Implementasi Kebijakan Pengelolaan Pendidikan Muhammadiyah Di Kabupaten Jeneponto - Hidayat Nur Wahid; Ihyani Malik; Ahmad Syarif (Universitas Muhammadiyah Makassar, 2026)
Abstract : This study aims to analyze the implementation of Muhammadiyah's education management policy in Jeneponto Regency and identify its supporting and inhibiting factors. The focus of the study refers to the Muhammadiyah Central Leadership Guidelines Number 1/Ped/I.0/B/2024 concerning Primary, Secondary, and Non-Formal Education. The research method used is qualitative with a descriptive approach. Data were collected through in-depth interviews with key informants from the Muhammadiyah Regional Leadership, the Elementary and Secondary Education Council, school principals, and students, as well as through observation and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions based on George C. Edwards III's policy implementation theory which includes variables of communication, resources, disposition, and bureaucratic structure. The results of the study show that the implementation of the policy has been carried out through intensive coordination between PDM and Muhammadiyah's Charity Enterprises, but still faces challenges in the aspects of resources and internal communication. The main supporting factors are the loyalty and high militancy of cadres in saving educational assets, as well as strong ideological support from the organization. Meanwhile, inhibiting factors include limited facilities, a shortage of specialized human resources, and internal conflicts at the local level that impact management stability. This study concludes that despite technical and financial constraints, the ideological commitment of cadres is a key pillar maintaining the existence of Muhammadiyah education in Jeneponto Regency. Keywords: Policy Implementation, Education Management, Muhammadiyah, Jeneponto